Effectiveness of Providing Education Using Leaflets on Knowledge and Compliance with Iron Supplement Tablet (IST) Consumption in Adolescent Girls at SMPN 1 Kromengan - Marindra Firmansyah; Gita Dwi Karisma; Yusuf Satrio Nugroho; Dinda Dwi Anggita; Faqihatul Azizah Devitasanti; Hafidh Nur Haq; Dewi Aminah (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to evaluate the effectiveness of providing education using leaflets on knowledge and compliance with Iron Supplement Tablet (IST) consumption in adolescent girls (rematri) at SMPN 1 Kromengan, Malang. The research design used was quasi-experimental with a pre-test and post-test design in the intervention group. The study sample consisted of 50 7th grade female students selected using a purposive sampling technique conducted for 5 days. The results showed that there was a significant increase in the level of knowledge and compliance with Iron Supplement Tablet (IST) consumption after education was provided through leaflets. The average knowledge score increased from the